An intriguing N-oxide-functionalized 3D flexible microporous MOF exhibiting highly selectivity for CO2 with a gate effect. (15th July 2020) - Kang, Yifan; Li, Zhihui; Wang, Yunluo; Chen, Yitong; Yang, Xiufang; Wen, Aiping
Graphical abstract: The axial chiral ligand 2, 2′-bipyridyl-3, 3′-dicarboxylic acid-1, 1′-dioxide (H2 bdd) has been employed to synthesize a 3D flexible microporous metal-organic framework (MOF), [Cu2 (bdd)2 (bpa)2 (H2 O)2 ]·6.5H2 On (1 ) (bpa = 1, 2-bis(4-pyridyl)ethane), which contains an N-oxide open donor site. A gas adsorption test shows that complex 1 ′ (dehydrated 1 ) has a high adsorption selectivity for CO2 rather than N2 and H2 . In particular, its CO2 adsorption isotherms exhibit an uncommon gate effect adsorption. The CO2 adsorption enthalpies were calculated from the adsorption isotherm. Compared to a flexible framework with respiration, 1 ′ displays a low energy consumption for sorbent regeneration, indicating the potential application of complex 1 in gas separation. Abstract: The axial chiral ligand 2, 2′-bipyridyl-3, 3′-dicarboxylic acid-1, 1′-dioxide (H2 bdd) has been employed to synthesize a 3D flexible microporous metal-organic framework (MOF), [Cu2 (bdd)2 (bpa)2 (H2 O)2 ]·6.5H2 On (1 ) (bpa = 1, 2-bis(4-pyridyl)ethane), which contains an N-oxide open donor site. A gas adsorption test shows that complex 1 ′ (dehydrated 1 ) has a high adsorption selectivity for CO2 rather than N2 and H2 . In particular, its CO2 adsorption isotherms exhibit an uncommon gate effect adsorption. The CO2 adsorption enthalpies were calculated from the adsorption isotherms. Compared to a flexible framework with respiration, 1 ′ displays a low energy consumption for sorbent regeneration, indicating the potential application of complex 1 in gas separation.